The Universe of Escherichia coli - Starčič Erjavec, Marjanca (IntechOpen, 2019)
The title of the book "The Universe of Escherichia coli" aims to present and emphasize the huge diversity of this bacterial species and our efforts to prevent the E. coli infections. As it is part of the gut microbiota, E. coli is a well-known commensal species, and probiotic E. coli strains are successfully used for improving host's health. Also many "workhorse" E. coli strain exist that are employed in laboratory and biotechnology settings. But certain E. coli strains can cause intestinal and also extraintestinal infections at many anatomical sites. Therefore many efforts are undertaken to prevent E. coli infections, among them food safety, vaccines, but also new antimicrobial agents are searched for.